Requirement of an Attitude Change for Coexistence among Sinhala and Tamil Ethnic Groups in the Post-war Context in Sri Lanka: A Study Based on the Students of the Universities of Colombo, Jaffna, Kelaniya and Eastern - Bandara, G.T.N.; Liyanage, D. (My University, 2015)
This research is about the requirement of an attitude change for coexistence between Sinhala and Tamil ethnic groups in post-war Sri Lanka. This study was carried out in order to identify how attitudes are constructed in a person's mind, how those attitudes influence behavior and what mechanism can be used to change attitudes. According to these factors, the study is in progress to analyze the nature of attitudes between Sinhala and Tamil ethnic groups. In addition, the threat of negative attitudes will be analyzed. The hypothesis of the research is that the nature of attitudes among Sinhala and Tamil ethnic groups in the post-war context in Sri Lanka has taken a negative trend. Questionnaires are used as the main research tool; interviews and participatory observation methods are also used. The sample population of the survey consisted of students from the University of Colombo, University of Kelaniya, University of Jaffna and the Eastern University. Fifty students participated from each university, making the total group two hundred. The main conclusion of this study is that changing attitudes towards coexistence is a vital requirement in the post-war context in Sri Lanka. Moreover, most Tamil people's attitude could be identified as negative towards the Sinhala people. But Sinhala people's attitudes are neither positive nor negative which is not harmful. The most significant finding was that there is a trend for both ethnic groups to have positive expectations for a strong friendship.
Keywords: Post-war, Sinhala and Tamil ethnic groups, Attitude development, Coexistence, University student